Self-refinement of Notch activity through the transmembrane protein Crumbs: modulation of gamma-Secretase activity. - Herranz, H.; Stamataki, E.; Feiguin, F.; Milan, M. (EMBO Reports, 2006)
Cell interactions mediated by Notch family receptors have been implicated in the specification of tissue boundaries. Tightly localized activation of Notch is crucial for the formation of sharp boundaries. In the Drosophila wing imaginal disc, the Notch receptor is expressed in all cells. However, Notch activity is limited to a narrow stripe of cells along the dorsal-ventral compartment boundary, where it induces the expression of target genes. How a widely expressed protein becomes tightly regulated at the dorsal-ventral boundary in the Drosophila wing is not completely understood. Here, we show that the transmembrane protein Crumbs is involved in a feedback mechanism used by Notch to refine its own activation domain at the Drosophila wing margin. Crumbs reduces the activity of the gamma-Secretase complex, which mediates the proteolytic intracellular processing of Notch. These results indicate a novel molecular mechanism of the regulation of Notch signal, and also that defects in Crumbs might be involved in similar abnormal gamma-Secretase complex activity observed in Alzheimer's disease.